2014
DOI: 10.3892/or.2014.3261
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of EGFR family gene aberrations in cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCA) is a highly lethal malignancy of the biliary tract with very few treatment options. Epidermal growth factor receptor (EGFR) and human epidermal growth factor receptor (HER2) have been considered as potential therapeutic targets in CCA. In the present study, we attempted to clarify the clinicopathological significance of all EGFR family members, EGFR, HER2, HER3 and HER4, across the full spectrum of CCAs. Immunohistochemistry and FISH were performed to validate expressions and genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 34 publications
2
45
2
4
Order By: Relevance
“…All four studies had a HQ HER3 expression assessment (Table 3). The pooled mean overall HER3 overexpression rate was 27.9 % (95 % CI 9.7–46.1 %) [51, 76, 81, 83]; only one study reported HER3 amplification rate (26.5 %) [83] (Table 2). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All four studies had a HQ HER3 expression assessment (Table 3). The pooled mean overall HER3 overexpression rate was 27.9 % (95 % CI 9.7–46.1 %) [51, 76, 81, 83]; only one study reported HER3 amplification rate (26.5 %) [83] (Table 2). …”
Section: Resultsmentioning
confidence: 99%
“…All of the four studies with HER3 expression data had HER2 expression data available for correlation analysis [51, 76, 81, 83]. No statistically significant correlation was identified between HER2 and HER3 overexpression (four studies; Spearman rho = 0.2; p value 0.8) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, ZnPC distributes to multiple intracellular loci after uptake of the liposomes [17, 18], from which different cell death pathways but also cell survival pathways are activated [2]. In preliminary experiments it was discovered that epidermal growth factor receptor (EGFR), a receptor overexpressed in a multitude of cancers [19] including perihilar cholangiocarcinoma [20, 21], was afflicted by PDT with ZnPC-liposomes. EGFR constitutes an important druggable target in cancer therapy, as evidenced by the approval status of the monoclonal antibodies cetuximab and panitumumab, as well as the kinase inhibitors gefitinib and erlotinib [22].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, mutations of ERBB4 have also been associated with multiple cancer types. 16,17 Therefore, to identify a possible role of ERBB4 in the development of platinum resistance, we sought to study ERBB4 expression by immunohistochemistry in clinical samples obtained from patients with complete response (CR) and incomplete response (IR) to platinum-based chemotherapy and ovarian cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%